2020
DOI: 10.3892/etm.2020.8506
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis in patients with idiopathic membranous nephropathy with hypertension

Abstract: The present study analyzed the clinicopathological features and prognosis in patients with idiopathic membranous nephropathy (IMN) with hypertension. In the hypertension group, significant differences were found in the age, hypertension history, systolic blood pressure, diastolic blood pressure (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We found individuals with ratios ≤4.25 were predominantly female, without hypertension, and had lower BMIs, DBPs, UAs and UPROs compared to those with higher ratios ( Supplementary Table S1 ). Although these features strongly associate with TA risk ( 5 , 33 , 36 38 ), their collective impact enhances among those with ratios >4.25, reducing the TG/HDL-C ratio’s effect. In contrast, with fewer impactful risk factors present below 4.25, the ratio’s influence is amplified—likely contributing to the nonlinear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…We found individuals with ratios ≤4.25 were predominantly female, without hypertension, and had lower BMIs, DBPs, UAs and UPROs compared to those with higher ratios ( Supplementary Table S1 ). Although these features strongly associate with TA risk ( 5 , 33 , 36 38 ), their collective impact enhances among those with ratios >4.25, reducing the TG/HDL-C ratio’s effect. In contrast, with fewer impactful risk factors present below 4.25, the ratio’s influence is amplified—likely contributing to the nonlinear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…As common pathological findings in renal diseases, intrarenal arterial lesions can be caused by many factors [2224]. Previous research mainly focused on general vascular abnormalities, glomerulosclerosis, and arteriolar hyalinosis in PMN [2528]. In this study, we focused on the intimal thickening of the intrarenal small arteries.…”
Section: Discussionmentioning
confidence: 99%
“…However, these guidelines lack renal pathology assessment indicators to aid in choosing treatment regimens. Many previous studies have highlighted the prognostic value of results of tubulointerstitial changes (fibrosis and cellular infiltration) [ 13 15 ], glomerular alterations with focal segmental sclerosis [ 16 ], and progressive histologic stage of electron-dense deposits [ 17 ], which are III to IV, according to the criteria of Ehrenreich et al [ 18 ]. Rosen et al [ 19 ] reported the division of subepithelial electron-dense deposits into 4 groups based on clinical and morphological configurations as short with 1 generation of deposits, short/repeated, long/rapid, and long/slow.…”
Section: Introductionmentioning
confidence: 99%